High-Throughput Virtual Screening for a New Class of Antagonist Targeting LasR of Pseudomonas aeruginosa - Vetrivel, Aishwarya (ACS Omega, 2021)
[Image: see text] Pseudomonas aeruginosa, an opportunistic human pathogen, causes fatal effects in patients with cystic fibrosis and immunocompromised individuals and leads to around 1000 deaths annually. The quorum sensing mechanism of P. aeruginosa plays a major role in promoting biofilm formation and expression of virulent genes. Hence, quorum sensing inhibition is a promising novel approach to treat these bacterial infections as these organisms show a wide range of antibiotic resistance. Among the interconnected quorum sensing network of P. aeruginosa, targeting the las system is of increased interest as its principal receptor protein LasR is the earliest activated gene. It is also shown to be involved in the regulation of other virulence-associated genes. In this study, we have applied high-throughput virtual screening, an in silico computational method to identify a new class of LasR inhibitors that could serve as potent antagonists to treat P. aeruginosa-associated infections. Three-tire structure-based virtual screening was performed on the Schrödinger small molecule database, which resulted in 12 top hit compounds with docking scores lesser than −11.0 kcal/mol. Three of these best-scored compounds CACPD2011a-0001928786 (C1), CACPD2011a-0001927437 (C2), and CACPD2011a-0000896051 (C3) were further analyzed. The binding free energies of these compounds in complex with the target protein LasR (3IX4) were evaluated, and the pharmacokinetic properties were determined. The stability of the docked complexes was assessed by running a molecular dynamics simulation for 100 ns. Molecular dynamics simulation analysis revealed that all three compounds were found to be in stable contact with the protein over the entire simulation period. The antagonistic effect of these compounds was validated using the LasR reporter gene assay in the presence of acyl homoserine lactone. Significant reduction in the β-galactosidase enzyme activity was achieved at 100 nM concentration for all three compounds pursued. Hence, the present study provides strong evidence that these three compounds could serve as quorum sensing inhibitors of P. aeruginosa LasR protein and can be a probable candidate to treat Pseudomonas-associated infections.